Perlakuan Udara Panas untuk Pengendalian Perkecambahan Spora Tilletia indica pada Gandum - Nurul Dwi Handayani; Taufan Tanto Setyawan; Salbiah Salbiah; Dono Wahyuno; Meity Suradji Sinaga (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Karnal bunt of wheat (Triticum aestivum) caused by Tilletia indica is a major concern in international trade because it can degrade quality significantly, and it is a quarantine pest for Indonesia. Tilletia infected seeds can be the source of fungal inoculum of other areas. The current research was aimed to determine the effectiveness of temperature and exposure time to control Tilletia using air heat treatment without reducing the quality of grain. The experiments were conducted in vitro, initiated by seed testing, including morphology-based detection and identification of Tilletia followed by a viability test of the seed. Air heat treatment was performed by adjusting the oven temperature at 75, 80, 85 °C and 28 °C (control) for 4 and 6 hr exposure time, each with three replications. The results showed that air heat treatment of the wheat at 75 °C for 4 hr was able to suppress teliospores germination of 56.7–61.7%, without denature protein content of the wheat.